PJMHS 2021
DOI: 10.53350/pjmhs211551214
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Partial and Complete Caries Excavation in Permanent Teeth: An 18 Months Follow-up

Abstract: Objective: To compare performance and survival of composite restorations in primary teeth using partial caries removal (PCR) versus complete caries removal (CCR). Methodology: In this trial, 70 permanent molars having deep caries lesions were selected and divided equally into CCR and PCR groups. The study duration was Jan-2018 to Jan-2020. In CCR group, complete dentin removal was done and confirmed by applying dentin detector dye for 10 seconds. In PCR group, visual & tactile criteria were followed for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Therefore, the remaining 5 articles met the eligibility criteria and were included in this study ( Table 1 ). The designs presented were: 5 randomized clinical trials [ 14 , 15 , 16 , 17 , 18 ] developed between 2010 and 2021 (k = 1). The flowchart diagram with the study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the remaining 5 articles met the eligibility criteria and were included in this study ( Table 1 ). The designs presented were: 5 randomized clinical trials [ 14 , 15 , 16 , 17 , 18 ] developed between 2010 and 2021 (k = 1). The flowchart diagram with the study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 , Table 3 and Table 4 show the characteristics of the included studies. The Ethics Committee approved all articles [ 14 , 15 , 16 , 17 , 18 ] that were selected before starting and registered for data protection. One was a single study [ 14 ], whereas the others presented guidelines for the study design.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations